ANALYZING THE INFLUENCE OF PERSONAL AND NON PERSONAL DETERMINANT FACTORS ON ENTREPRENEURSHIP INTENTION OF BUSINESS AND ENGINEERING STUDENTS - SRI AGUSTINI (29009013) ; pembimbing : Dwi Larso Ph.D., ENDANG
Since entrepreneurship is considered as an economic engine, the researchers began to investigate the factors that influence a person's entrepreneurial activity. At the level of students who remained in the study period, entrepreneurial behavior is still planned (the intention). This study used the framework of the Theory of Planned Behavior (TPB) Model developed by Ajzen (1991). This framework is relevant to the purpose of research that assesses personal factors, are also environmental factors that influence the intention of Business Management and Engineering Students. This theory is partially able to predict entrepreneurial intentions. Entrepreneurial Self-efficacy is the strongest predictor of entrepreneurial intentions for both groups of students were studied. The test results using path analysis and trimming technique on the 8 (eight) variables revealed a different pattern of effects in both groups of students were studied. Risk-taking propensity is the most dominant personal factors indirectly affect of the entrepreneurial intention of both groups of students. While the locus of control only affects on entrepreneurial intentions of Business Mangement Students group. Entrepreneurship Education were also seen its influence, only teaching method that has a positive effect through the mediation of Attitude Toward Entrepreneurship, and even then only in the Business Management Students. Social values towards entrepreneurship is also the most influential factor on entrepreneurial intentions both groups of students, while the government's role is perceived by the students of Engineering has a direct impact on their entrepreneurial intentions. In contrast to previous research, this study shows that students of Engineering more entrepreneurial than the Business Management Student. Female students in this study have also been confirmed more entrepreneurial, while students with entrepreneurial parents better to have higher intentions towards entrepreneurship than other work settings of their parents.